Factors that Affect the Feeling of Happiness in Israel - ADI , Ben David Nissim Berko; IDIT , David (Asian Journal of Empirical Research, 2013)
In this paper, we analyzed the answers to questionnaires distributed among 140 people in Israel and identified the main factors that have an affect over feeling of happiness’. We estimated an econometric equation with happiness as the dependent variable. Our findings show that feeling of happiness’ among women is mainly affected by satisfaction from marital status; a variable that also has a large effect on males’ sense of happiness. Among men, the most important factor is satisfaction during time leisure, a factor which also has a positive effect on female happiness. Other factors which have a negative affect only on males are higher age, higher education and higher income, while more hours sleeping increases happiness among males.